2018
DOI: 10.1186/s41239-017-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of previous studies on ESL/EFL learners’ interactional feedback exchanges in face-to-face and computer-assisted peer review of writing

Abstract: This paper is a review of previous studies on learners' interactional feedback exchanges in face-to-face peer review (FFPR) and computer-assisted peer review (CAPR) of English as Second/Foreign Language (ESL/EFL) writing. The review attempted to (1) identify the patterns of interactional feedback, (2) search an empirical evidence of learners' incorporation of peer interactional feedback in their text revisions and (3) identify the factors affecting learners' interactional feedback as reported in these previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…The results revealed that the revisionoriented comments were more prevalent in both MMPR and FFPR groups. The existence of revision-oriented comments in this study shows that the participants remained on the task and aimed at various problems in their peers' writings (Saeed, Ghazali, & Aljaberi, 2018). This is in line with other previous studies which reported that students in technology-enhanced environments take part more in making revisionoriented peer review (Bradley, 2014;Ho, 2015;Liou & Peng, 2009;Pham & Usaha, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that the revisionoriented comments were more prevalent in both MMPR and FFPR groups. The existence of revision-oriented comments in this study shows that the participants remained on the task and aimed at various problems in their peers' writings (Saeed, Ghazali, & Aljaberi, 2018). This is in line with other previous studies which reported that students in technology-enhanced environments take part more in making revisionoriented peer review (Bradley, 2014;Ho, 2015;Liou & Peng, 2009;Pham & Usaha, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The least effective mode of PR was online PR during class time. While the informants' preferences to in-person review has echoes in some previous studies (Ho, 2015;Liu & Sadler, 2003), this finding contradicts the findings of many other studies (Breuch, 2004;Huang, 2016;Saeed et al, 2018;Vorobel & Kim, 2017). 3 & 4) reveal only two significant differences between the groups.…”
Section: Effective Formats Of Prcontrasting
confidence: 66%
“…In a more elaborated study, Saeed, Ghazali, and Aljaberi (2018) traced the development of relevant research in L2 writing from 1990 to 2016. The author reviewed 37 studies on feedback exchange in F2F and online PR.…”
Section: Online Vs Face-to-face Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on feedback for EFL learning in computer-mediated (CM) environments has widely focused on peer feedback, often on EFL writing (Guardado and Shi, 2007;Ho, 2015;Saeed et al, 2018). Jiang and Ribeiro (2017) present a systematic literature review on the effect of CM peer-written feedback on adult EFL writing.…”
Section: Previous Workmentioning
confidence: 99%